2019
DOI: 10.1017/s0007485319000609
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the behaviour modifying activity of two natural sesquiterpenoids farnesol and nerolidol towards Myzus persicae (Sulzer) (Homoptera: Aphididae)

Abstract: The effect of structurally related sesquiterpenoids (E,E)-farnesol and cis-nerolidol on the host-plant selection behaviour of the peach potato aphid Myzus persicae (Sulz.) was evaluated using electrical penetration graph (EPG) technique. No repellent effects of (E,E)-farnesol and (Z)-nerolidol to M. persicae were found but aphid probing activities on (E,E)-farnesol- and cis-nerolidol-treated plants were restrained. During non-phloem phases of probing, neither (E,E)-farnesol nor (Z)-nerolidol affected the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Under natural conditions, the high proportion of salivation during the consumption of the phloem sap is typical for aphid behavior on unsuitable or non-host plants [51][52][53]. Similar effects on aphid behavior during the phloem phase were revealed when aphids were offered plants treated with natural and synthetic compounds, e.g., piperitone-derived lactones, cis-jasmone and its derivatives, β-thujone and its derivatives, or farnesol and nerolidol [32,[54][55][56]. The settling deterrent activities of β,γ-dimethyllactone (4) and α,γ-dimethylenelactone (7) were probably due to the post-ingestive inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…Under natural conditions, the high proportion of salivation during the consumption of the phloem sap is typical for aphid behavior on unsuitable or non-host plants [51][52][53]. Similar effects on aphid behavior during the phloem phase were revealed when aphids were offered plants treated with natural and synthetic compounds, e.g., piperitone-derived lactones, cis-jasmone and its derivatives, β-thujone and its derivatives, or farnesol and nerolidol [32,[54][55][56]. The settling deterrent activities of β,γ-dimethyllactone (4) and α,γ-dimethylenelactone (7) were probably due to the post-ingestive inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…However, the content and distribution of individual secondary metabolites vary greatly among plant genotypes [41]. Here, the important roles of zeatin, sesquiterpenoid [42] and triterpenoid [43], carotenoid and diterpenoid [44], monoterpenoid [45] and phenylpropanoid [46] were also highlighted by the existence of a large number of upregulated genes involved in the synthesis of these chemicals in Caoyuan No.4, which indicated that thrips defense in Caoyuan No.4 was related to the existence of certain secondary metabolites. It is well known that the interaction of plant-pathogen and plant-insects share some strategies.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, 117 genes shared in both S_CK vs S_T group and S_CK vs R_CK group were mainly related to secondary metabolism, fatty acid metabolism, amino acid metabolism, rust resistance kinase, WRKY transcription factor and nodule lectin. Thus, a majority of genes were probably associated with the plant induced defense to herbivorous insects [40][41][42][43][44][45][46][47][48][49][50][51][52]. In addition, the other 2087 DEGs only expressed in Caoyuan No.4 were mainly constitutive defensive genes, which are involved in energy metabolism, carbohydrate metabolism and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The EPG technique provides a unique opportunity to reveal aphid mouthparts stylets activities in plant tissues [ 41 , 42 , 43 ]. The parameters describing aphid behavior during probing and feeding, such as total time of probing, duration and frequency of sap ingestion periods, number of probes, etc., are good indicators of plant suitability or interference of probing by chemical or physical factors in individual plant tissues [ 16 , 17 , 18 , 19 , 20 ]. In this experimental setup, aphid and plant are made parts of an electric circuit, which is completed when the aphid inserts its stylets into the plant.…”
Section: Methodsmentioning
confidence: 99%
“…), which may cause the withdrawal of the herbivore from the plant or other substrates, are searched for [ 13 , 14 , 15 ]. The exogenous application of xenobiotics may alter aphid response to otherwise acceptable host plants, which has been shown in studies on aphid antifeedants involving different chemical groups, including terpenoids, quassinoids, flavonoids, and cyanogenic glycosides [ 9 , 16 , 17 , 18 , 19 , 20 ]. At the same time, aphids may be attracted to other areas, such as trap crops or barrier crops, in ‘push–pull’ strategies [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%